Potensi dan Pengembangan Anak-Anak Pesisir Purus - azmi fitrisia; Rahmuliani Fithriah (Jurusan Sejarah FIS UNP, 2021)
The article aims to discover the potential of purus coastal children. It will try to study the efforts in exploring the potential. Certainly in relation to efforts to develop themselves in the hope of having a better for future. An important question of this article is how are the coastal children of Purus capable?. How is the strategy to explore talent? This research uses library method, observation and interview with children of fishermen in Purus, West Padang District, Padang City. There were approximately 10 informants interviewed. Observations were made gradually in 2019-2020. The results of this study show that children on the coast of Purus have a lot of potential. They have the potential to tell storytelling, play theater and write. They have been able to tell story and also play theater. Children on the coast also have potential in the field of writing. Some of the strategies tried on Purus coastal children are encouraging them to talk/tell stories, provide knowledge, practice and develop reading interests. The potential of coastal children in Purus needs to be continuously fostered because it is very difficult to expect their poor and poor parents. The Challenging challenge.